Characteristics of laboratory findings of COVID-19 patients with comorbid diabetes mellitus. (September 2020) - Jing Liang, Jing; Liu, Jun; Chen, Yong; Ye, Bo; Li, Na; Wang, Xiao; Tang, Min; Shao, Jiaqing
Abstract: Aims: Coronavirus disease (COVID-19), also referred to as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is instigated by a novel coronavirus. The disease was initially reported in Wuhan, China, in December 2019. Diabetes is a risk factor associated with adverse outcomes. Herein, our objective was to investigate the characteristics of laboratory findings of type 2 diabetes mellitus (T2DM) patients infected with SARS-CoV-2. Methods: This was a retrospective study and included 80 T2DM patients of Jinling Hospital from 2010 to 2020, as well as 76 COVID-19 patients without T2DM and 55 COVID-19 patients with T2DM who were treated at Huoshen hill Hospital from February 11 to March 18, 2020. We then compared the differences in laboratory test results between the three groups. Results: The levels of lymphocytes, uric acid (UA), and globulin in the T2DM group were significantly higher. In contrast, C-reactive protein (CRP), creatinine, and lactic dehydrogenase (LDH)levels were lower than those in the COVID-19 (p < 0.05) and COVID-19 + T2DM groups (p < 0.05). No considerable difference was observed regarding the levels of alanine aminotransferase (ALT), white blood cell (WBC), aspartate aminotransferase (AST), globulin, and blood urea nitrogen (BUN) in the three groups (p > 0.05). Conclusion: T2DM patients infected with SARS-CoV-2 showed decreased levels of body mass index (BMI), lymphocytes, UA, and albumin, and increased CRP levels. The decreased BMI, UA, and albumin levels may be associated with oxidative stress response and nutritional consumption. The decreased lymphocyte counts and increased CRP levels may be related to the infection.